Copper in Peru: Present status and future challenge - Acosta Ale, Jorge Gilberto (2013)
The copper mineralization in Peru is intimately associated with porphyry Cu deposits and subdivides into three porphyry Cu belt as Paleocene, Eocene-Oligocene, and Miocene. Up to now, the total copper production from them reach 28 Mt Cu. The total copper production from the Paleocene Cu belt, including Toquepala, Cuajone, and Cerro Verde, accounts for approximately 57% of total copper production from Peru. But focusing mineral exploration on middle southern (Eocene-Oligocene) and northwestern part (Miocene) of Peru results in new discoveries, including La Granja, El Galeno, Las Bambas, Toromocho, and Rio Blanco, which have an estimated annual production more than 200,000 t Cu. In addition to them, thirteen Cu deposits are discovered from the Paleocene, Eocene-Oligocene, and Miocene Cu belts. Thus, Peru is supposed to produce Cu production from 2014 and increases annual production from 143 Mt Cu in 2012 to 490 Mt Cu in 2019. Due to new discoveries, it is expected that mineral exploration activities in Peru are likely to move from Paleocene Cu belt to Eocene-Oligocene and Miocene Cu belts.